RNAi Screening of the Kinome Identifies PACT as a Novel Genetic Modifier of Foci Integrity in Myotonic Dystrophy type 1 - O'Reilly, Sean W.P. (Université d'Ottawa / University of Ottawa, 2014)
Myotonic Dystrophy type 1 (DM1), the most common form of adult muscular dystrophy (~1:8000) currently has no effective treatment. In DM1, expansion of a tri-nucleotide repeat in the 3' UTR of the DMPK gene results in DMPK mRNA hairpin structures, aggregating as insoluble ribonuclear foci. The resulting mis-regulation of important splicing factors, causes the inclusion of fetal exons in dozens of transcripts that contribute to the disease phenotype. In order to identify novel gene targets and kinase signalling pathways for potential therapeutics we have performed a high-throughput RNAi. RNA foci were visualized and quantified by in-situ hybridization. From our screen, we have identified a novel gene, PACT, as a modulator of foci integrity and that PACT knockdown can induce MBNL1 protein levels. The identified signalling complex represents a valid target for DM1 therapeutics. Our data further emphasizes the utility of RNAi screens in identifying disease-associated genes.
Keywords: RNAi; Muscular Dystrophy; Myotonic Dystrophy; PACT; DMPK; MBNL1